Critical Discourse Analysis of Dua Garis Biru Novel (Novel Adaptation of Lucia Priandarini from Gina S. Noer's Scenario) - Putri, Meidiana; Mardikantoro, Hari Bakti; Baehaqie, Imam (Universitas Negeri Semarang, 2022)
Language has a very important role in human life. As a tool for communication, language can be used in various ways, including through literary works in the form of novels. The purpose of this study is to identify and analyze the discourse of the characters in the novel